EVALUASI MUTU YOGURT FORMULASI SUSU JAGUNG MANIS KEDELAI - Setiawati, Bernadetta Budi; Puspitojati, Endah (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2011)
Yoghurt is a fermented food product produced worldwide using co-cultures of two species of lactic acid bacteria; streptococcus thermophilus and Lactobacillus bulgaricus. Study was carried out to evaluate the quality in chemical and sensory characteristics of plain yoghurt produced from sweet corn-soybean milk mixing during 15 days refrigerated storage. The reduction in pH can be due to breakdown of lactose into lactic acid. The lag time for the pH decrease during storage reflected the acidification rate of the culture involved. Yoghurt quality is therefore affected due to microbial growth. The pH value was 4 - 4,15. Organoleptic examination showed that yoghurt produced from sweet corn-soybean milk mixing in t ; l formulation had the highest acceptable degree in color, flavor, taste and consistency. The most favored yoghurt was then observed for its nutrient contents consisting water, ash, fat, protein, fiber, totat sucrose, vitamin C, vitamin A, and minerals. The water content of yoghurt was lower than soyghurt, meaning yoghurt had higher total solids, indicating that it was more nutritious than soyghurt. The fat content in the corn-soybean milk mix yoghurt was 0.44 I o%, therefore suitable in supporting diet programs. The results showed that Na content of the sweet corn-soybean milk mixing yoghurt was I146,54 ppm and Fe content was 10,075 ppm.